Highest heterogeneity for cystic fibrosis: 36 mutations account for 75% of all CF chromosomes in Turkish patients - (:unkn) unknown (WILEY-LISS, 2002)
We analyzed the CFTR locus in 83 Turkish cystic fibrosis patients to identify mutations, haplotypes, and the carrier frequency in the population. We detected 36 different mutations in 125 (75%) of the total 166 CF chromosomes. Seven novel mutations were identified: four missense (K68E, Q493P, E608G, and V1147I), two splice-site (406-3T > C and 3849 + 5G > A), and one deletion (CFTRdele17b,18). The data showed that the Turkish population has the highest genetic heterogeneity at the CFTR locus reported so far. The results of this thorough molecular analysis at the CFTR locus of a population not of European descent shows that CF is not uncommon in all such populations. The large number of mutations present, as well as the high heterogeneity in haplotypes associated with the mutations suggests that most of the mutations have persisted for a long time in the population. Consistently, the carrier frequency is assessed to be high, indicating that the disease in the population is ancient. (C) 2002 Wiley-Liss, Inc.
Keywords: CF; Turkish; K68E; Q493P; E608G; V1147I; 406-3T > C; 3849+5G > A; CFTRdele17b, 18; TRANSMEMBRANE CONDUCTANCE REGULATOR; EUROPEAN POPULATIONS; SPLICE-SITE; GENE; IDENTIFICATION; ORIGIN; REGIONS; ALLELES; DISEASE; ASSOCIATION